Higiene Sanitasi Rumah Makan di Kelurahan Sendangan Kecamatan Kawangkoan Kabupaten Minahasa Tahun 2019 - Assa, Yunita M.; Boky, Harvani; Umboh, Jootje M. L. (e-Biomedik, 2019)
Abstract: Food sanitation is one of the prevention efforts that focus on activities and actions to relieve food and drinks from all hazards to health. This study was aimed to obtain the hygiene sanitation of restaurants at Sendangan, Kawangkoan. This was a descriptive study. The population consisted of all restaurants located at Sendangan. Food sanitation hygiene in this study was according to Kepmenkes RI No. 1098/MENKES/SK/VII/2003. The results showed that there were six restaurants involved in this study. The scores of restaurant hygiene and sanitation for location and buildings showed one restaurant with a total score of 38 (not fulfilled the requirements); 66 for sanitation facilities in the restaurants (did not meet the requirements); 38 for kitchen, dining room, and food storage warehouse, meanwhile 110 for food and ready-made food (eligible); 10 for food processing (did not meet the requirements); 58 for storage of food and ready-made food at one dining house (not fulfilled the requirements); 40 for serving meals at all restaurants (fulfilled the requirements); 45 for the equipment in all restaurants (eligible); 14 for the workers at the restaurant (did not meet the requirements). In conclusion, most of the restaurant fulfilled the requirement on food ingredients, cooked food, as well as food serving and utilities.Keywords: hygiene, sanitation, restaurantsÂ Abstrak: Sanitasi makanan adalah salah satu usaha pencegahan yang menitik beratkan pada kegiatan dan tindakan untuk membebaskan makanan dan minuman dari segala bahaya yang dapat menganggu kesehatan. Penelitian ini bertujuan untuk mengetahui higiene sanitasi rumah makanan di Kelurahan Sendangan Kecamatan Kawangkoan. Jenis penelitian ialah deskriptif. Populasi ialah seluruh rumah makan yang berada di Kelurahan Sendangan. Higiene sanitasi makanan ialah menurut Kepmenkes RI N0.1098/MENKES/SK/VII/2003. Terdapat enam rumah makan yang terlibat dalam penelitian ini. Hasil skor higiene dan sanitasi rumah makan pada lokasi dan bangunan rumah makan mendapatkan satu rumah makan dengan skor total berjumlah 38 (tidak memenuhi syarat); fasilitas sanitasi rumah makan berjumlah 66 (tidak memenuhi syarat); dapur, ruang makan dan gudang bahan makanan berjumlah 38, bahan makanan dan makanan jadi berjumlah 110 (memenuhi syarat); pengolahan makanan rumah makan berjumlah 10 (tidak memenuhi syarat); penyimpanan bahan makanan dan makanan jadi pada satu rumah makan berjumlah 58 (tidak memenuhi syarat); penyajian makanan 40 di semua rumah makan (memenuhi syarat); peralatan terdapat di semua rumah makan berjumlah 45 (memenuhi syarat); dan tenaga kerja pada rumah makan berjumlah 14 (tidak memenuhi syarat). Simpulan penelitian ini ialah sebagian besar rumah makan sudah memenuhi syarat pada bahan makanan, makanan jadi, penyajian makanan, dan peralatan.Kata kunci: higiene, sanitasi, rumah makan